BBARHS: Blockchain-Based Anonymous Ride-Hailing Scheme for Autonomous Taxi Network. (9th August 2022) - Wang, Kun; Liu, Mingzhe; Wang, Jianping; Wu, Min; Zhao, Feixiang
Abstract : In the past few years, ride-hailing platforms such as Uber, Waymo, and Baidu have built their own autonomous taxi system. Unlike public transit services, ride-hailing platforms raise severe privacy issues. To provide excellent autonomous taxi service, some significant security and privacy problems must be addressed. In this study, we present the security and privacy threats and first proposed blockchain-based anonymous ride-hailing scheme (BBARHS) for autonomous taxi network. We give the formal system model and security model of BBARHS. Then, we outline the concrete BBARHS scheme by making use of Monero and some efficient crypto tools. Through security analysis and performance analysis, the designed scheme is provably secure and efficient. The analysis results also show the designed BBARHS scheme is practical for autonomous taxi network.